2008
DOI: 10.2337/db08-0753
|View full text |Cite
|
Sign up to set email alerts
|

A Human Type 1 Diabetes Susceptibility Locus Maps to Chromosome 21q22.3

Abstract: OBJECTIVE— The Type 1 Diabetes Genetics Consortium (T1DGC) has assembled and genotyped a large collection of multiplex families for the purpose of mapping genomic regions linked to type 1 diabetes. In the current study, we tested for evidence of loci associated with type 1 diabetes utilizing genome-wide linkage scan data and family-based association methods. RESEARCH DESIGN AND METHODS— A total of 2,496 multiplex families with type 1 diabetes were genotyped with a panel of 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
82
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 34 publications
9
82
0
1
Order By: Relevance
“…Currently 15 loci have been identified that have convincing evidence for association with T1D. [1][2][3][4] Interestingly, several of these T1D susceptibility loci are shared with other immune-mediated diseases, namely PTPN22, CTLA4, IL2RA, IL2, IL7R and SH2B3 (see Table 1 for full gene names). 1,5,6 Therefore, we sought to test newly identified rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), multiple sclerosis, ankylosing spondylitis (AS) and Crohn's disease (CD) loci for association in T1D [7][8][9][10][11][12][13][14][15][16][17] with the assumption of an increased prior probability of association based on the previous evidence of overlapping risk alleles across autoimmune diseases.…”
mentioning
confidence: 99%
“…Currently 15 loci have been identified that have convincing evidence for association with T1D. [1][2][3][4] Interestingly, several of these T1D susceptibility loci are shared with other immune-mediated diseases, namely PTPN22, CTLA4, IL2RA, IL2, IL7R and SH2B3 (see Table 1 for full gene names). 1,5,6 Therefore, we sought to test newly identified rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), multiple sclerosis, ankylosing spondylitis (AS) and Crohn's disease (CD) loci for association in T1D [7][8][9][10][11][12][13][14][15][16][17] with the assumption of an increased prior probability of association based on the previous evidence of overlapping risk alleles across autoimmune diseases.…”
mentioning
confidence: 99%
“…For example, the HLA-DQ8 (DQB*03:02) and DQ2 (DQB*02:01 and DQB*02:02) alleles greatly increase the risk of disease development, with ∼90% of all T1D individuals having one or both alleles (14)(15)(16). Strikingly, the polymorphic HLA-DQ6 (DQB*06:02) allele provides dominant protection from diabetes development (14).…”
mentioning
confidence: 99%
“…In humans, particular HLA alleles are also associated with T1D, explaining more than 50% of the genetic risk for disease development (14). For example, the HLA-DQ8 (DQB*03:02) and DQ2 (DQB*02:01 and DQB*02:02) alleles greatly increase the risk of disease development, with ∼90% of all T1D individuals having one or both alleles (14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several IFIH1 polymorphisms were associated with T1DM, with the rs1990760 (G/A) polymorphism, which substitutes an alanine to valine in codon 946 of exon 15, being most strongly associated with protection against development of the disease (odds ratio [OR] = 0.86, P = 1.42 x 10 -10 for the G allele) (50). Associations between IFIH1 polymorphisms and T1DM have been replicated in some populations (29,(51)(52)(53)(54)(55), but not in others (56)(57)(58) (Table 1). Jermendy and cols.…”
Section: Ifih1 Gene Polymorphisms and Their Association With T1dmmentioning
confidence: 92%